2017
DOI: 10.1007/s00240-017-1012-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative double-J stent placement can improve the stone-free rate for patients undergoing ureteroscopic lithotripsy: a systematic review and meta-analysis

Abstract: To evaluate the efficiency and safety of preoperative double-J stent placement for patients undergoing ureteroscopic lithotripsy. Eligible studies were identified from electronic databases (PubMed, Embase, the Cochrane Central Register of Controlled Trials, and the Cochrane Database of Systematic Reviews). All analyses were performed by the Review Manager 5.3 (The Cochrane Collaboration, Oxford, UK). Stone-free rate (SFR) was regarded as primary outcome. Second outcomes, including operation time, complication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 14 publications
8
22
0
Order By: Relevance
“…The analysis demonstrated a higher stone free rate for pre-stented renal stones, but no benefit for ureteric stones [28] . These results were confirmed in a recent meta-analysis of nine retrospective studies, including 11 239 patients, identifying a stone-free rate in favour of pre-stented patients (OR [95%CI]: 1.6 [1.19, 2.15]) [29] .…”
Section: Indicationsmentioning
confidence: 54%
“…The analysis demonstrated a higher stone free rate for pre-stented renal stones, but no benefit for ureteric stones [28] . These results were confirmed in a recent meta-analysis of nine retrospective studies, including 11 239 patients, identifying a stone-free rate in favour of pre-stented patients (OR [95%CI]: 1.6 [1.19, 2.15]) [29] .…”
Section: Indicationsmentioning
confidence: 54%
“…Preoperative ureteral stenting may affect the success rate of the URS. A meta-analysis of nine retrospective studies with a total of 11,239 patients showed a higher SFR if the patient had received a preoperative ureteral stent [25], confirmed in other studies [26]. If the positive effect on SFR by preoperative stenting is due to stone location / stone burden or by stenting itself, remains unclear [9].…”
Section: Discussionmentioning
confidence: 87%
“…1a). Pre-stenting can improve the passive dilation of the ureter and increase the stone-free rate during URSL [11,12]. It has been reported that bacteriuria and bacterial colonization of the stent occurs over time after stent placement [13].…”
Section: Discussionmentioning
confidence: 99%